Odpowiedź:
[tex]a) (2,2^{2} +1)-( 2,2^{2}-2,2)+10 = \\((\frac{11}{5}) ^{2} +1)-((\frac{11}{5})^{2} -2,2)+10=\\(\frac{11}{5} )^{2}+1-\frac{11}{5})^{2}+2,2 +10 = 13,2[/tex]
[tex]b)(-0,1+0,8)-(5+0,2)-(0,6-5)=[/tex]
[tex]0,7-5,2-(-4,4)[/tex]
[tex]0,7-5,2+4,4 = -0,1[/tex]
[tex]c) (-\frac{1}{16} +(-1)-1)+(\frac{1}{6} -(-2)+5)=[/tex]
[tex](-\frac{1}{16} -1-1)+(\frac{1}{6} +2+5)[/tex]
[tex](-\frac{1}{16} -2)+(\frac{1}{6} +7)[/tex]
[tex](-\frac{33}{16} +\frac{43}{6}) = \frac{245}{48}[/tex]
Szczegółowe wyjaśnienie:
Nie jestem pewna w ostatnim....